ANALISIS SALURAN PEMASARAN CABAI RAWIT (Capsicum Frutescens. L) (Studi kasus di Kecamatan Kanigoro, Kabupaten Blitar) - Sofanudin, Ahmad; Budiman, Eko Wahyu (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2017)
Marketing is an economic activity which functions to deliver goods from producers to consumers. The large number in agencies marketing of Capsicum annuum will bring effect the length of the marketing chain and the cost of marketing.This research was conducted in Kanigoro District of Blitar Regency with the purpose of study marketing pattern of Capsicum annuum, analyzing marketing margin, performing function in every agency marketing and analyzing efficiency of marketing channel. Marketing of Capsicum annuum in Kanigoro sub-district consists of three marketing channels namely first channel (I); Farmer-collector-consumer. Second channel (II); Large farmer-farmer farmers-retailer-consumer farmers. The third channel (III); Big farmers-retailer-consumer farmers. The amount of marketing cost of Capsicum annuum must be issued by collecting traders Rp 3,000 per kg on channel I, traders Rp 3,500 per kg on channel II and Rp 3,500 per kg on channel III. The amount of profit received by the collector / middleman Rp 3,500 per kg on channel I. Collector traders Rp 2.500 per kg, wholesalers Rp 1.500 per kg, retailers Rp 2,500 per kg on channel II. Large traders Rp 3.500 per kg, retailers Rp 2,500 per kg on channel III. The marketing margin value of Capsicum annuum is Rp 6,500 per kg on channel I, Rp 10,000 per kg on channel II and Rp 10,000 per kg in channel III. And share the price received by farmers amounting to 75% on channel I, 67% on channel II and 67% on channel III.